EFEKTIVITAS PENGGUNAAN MODEL THINK TALK WRITE DISERTAI HANDOUT TERHADAP HASIL BELAJAR SISWA MAN 2 PONTIANAK - Fitriani, Fitriani; Putri Panjaitan, Ruqiah Ganda; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe study aims to know how well the effectiveness of the use Think Talk Write (TTW) cooperative learning model with handout on the students learning result in grade XIth of MAN 2 Pontianak on nervous system sub material. The research design was conducted through quasi experiment with nonequivalent control group design. The sampling technique used saturated sampling with the samples are XI MIPA 2 as control class and XI MIPA 3 as experiment class. Handouts was validated and analyzed by using the Gregory formula with the result is 1.00 (very high criteria).Â  Scores of the students learning outcomes taught by using Think Talk Write (TTW) cooperative learning model with handout is 15.54, higher than the score of students learning outcomes taught by using conventional learning model which only 13.77. After the U Mann-Whitney test, it is known that Zcount<Ztable (-4.06 <- 1.96) means that there is a significant difference between the experimental class and the control class at the 5% level. Based on the calculation of effect size, the score is 0.84 (high criteria), and from the normal curve standard, the learning by using Think Talk Write (TTW) cooperative learning model with handout contributes 29.96% to the students learning outcomes.Keywords: Eeffectiveness,Level of Validity, Think Talk Write (TTW), Handouts, Nerves System